Experimental Study on Mechanical Properties on Ternary Blend of Concrete - Chander S, Vijay; K, Ramakrishnan; D, Muthu (International Journal of Engineering and Technology, 2018)
A major problem in cement manufacturing is the increased emission of CO2. About 5% of worldwide man-made emission of CO2 is generated. Cement being the predominant material of concrete, the usage needs to be reduced by using admixtures or SCMs to replace partially, the percentage of OPC in concrete. Admixtures like Metakaolin (MK) and Waste Glass Powder (GP) were used to replace OPC, producing a ternary blended concrete. The cement replacement with GP is from 5% to 45% and MK is from 45% to 5% both in steps of 5% and hence a total of ten combinations including control mixture (100% cement) were studied for M30 grade. Mechanical properties are evaluated by conducting compressive, split tensile strength tests. The initial compressive strength of mix containing 20% GP and 30% MK with 50% OPC, after 7 days curing is found to be higher by 5%, compared with control mix.Â